Pengaruh Pemberian Porasi Janjang Kosong dan Dolomit terhadap Pertumbuhan dan Hasil Tanaman Bayam Merah - Salampak, Salampak; Sustiyah, Sustiyah; Anwar, Moch; Beladona, Siti Unvaresi Misonia; Hartoko, Galih; Wahyuningtyas, Meylinda Dwi (Universitas Lampung, 2024)
The utilization of peat soil as a planting medium is still faced with several problems, especially in terms of the chemical characteristics of peat soil. Therefore, there is a need for treatment to improve these problems, one of which is by using the poration of palm oil empty fruit bunches and dolomite. This research aims to determine the effect of providing a technology package of empty fruit bunch and dolomite poration doses on the growth and yield of red spinach plants. The research was carried out at the Greenhouse Jalan G. Obos 24, for 3 months (September-November 2023). The research was carried out using a survey method and experimental tests in polybags, using the RAL method with 9 treatment technology packages, namely: 1) soil without treatment (control), 2) Soil + empty fruit bunches poration 2.5 tons ha-1 + dolomite 2 tons ha-1, 3) Soil + 2.5 tons ha-1 of empty fruit bunches poration + 4 tons of ha-1 dolomite, 4) Soil + 5 tons of ha-1 of empty fruit bunches poration, 5) Soil + 5 tons ha-1 of empty fruit bunches poration + 2 tons ha-1 dolomite, 6) Soil + empty fruit bunches poration 5 tons ha-1 + dolomite 4 tons ha-1, 7) Soil + empty fruit bunches poration 7.5 tons ha-1, 8) Soil + empty fruit bunches poration 7.5 tons ha-1 + dolomite 2 tons ha-1 , 9) Soil + empty fruit bunches poration 7.5 tons ha-1 + dolomite 4 tons ha-1. The variables observed included plant height, stem diameter, root length, plant wet weight, and plant dry weight. Providing a package of peat soil + 7.5 tons ha-1 of empty fruit bunches poration + 4 tons of ha-1 dolomite (T(8)) can increase the growth of red spinach plants which include plant height (4.46 – 37.36 cm), stem diameter (4.48 – 7.06 cm), the wet weight of the plant is 26.10 g/polybag. Keywords : poration, dolomite, plant height, palm oil empty fruit bunch